Snake venomics and antivenomics: Proteomic tools in the design and control of antivenoms for the treatment of snakebite envenoming - Gutiérrez, José María (2009)
Snakebite envenoming represents a neglected tropical disease that has a heavy public health impact, particularly in Asia, Africa and Latin America. A global initiative, aimed at increasing antivenom production and accessibility, is being promoted by the World Health Organization and others. This work discusses several aspects of antivenom manufacture and control in which the proteomic analysis of snake venoms, for which the term ‘snake venomics’ has been coined, might play a relevant supporting role. Snake venomics has already shown its usefulness for generating knowledge at different levels (ontogenetic, individual, and geographic) on inter- and intraspecies venom variability. This information has applications for the quality control of venom preparations used in antivenom manufacture. Moreover, the design of the best venom mixtures for immunization, aimed at increasing the effectiveness of antivenoms, may also be guided by venom proteome analysis, including molecular studies of the cross-reactivity of antivenoms and heterologous venoms through a recently developed methodological approach termed ‘antivenomics’. Results generated by proteomic protocols should be complemented by preclinical testing of antivenom efficacy using functional neutralization assays. Snake venomics might be also helpful in designing alternative in vitro tests for the assessment of antivenom efficacy that would eventually substitute current in vivo tests.